Analisis Kemampuan Pemecahan Masalah Aljabar Boolean Berdasarkan Kemampuan Awal dan Problem Based Learning - Rini Widia Putri Z; Purni Munah Hartuti; Roni Al Maududi (SAP (Susunan Artikel Pendidikan), 2022)
One of the reasons for the low problem-solving ability in Boolean algebra material is that students are not used to solving problem-based questions. To work on problem-based questions, students must have initial abilities. Thus, this study aims to determine the effect of initial abilities on problem solving abilities, determine the effect of the Problem Based Learning (PBL) model on problem solving abilities, and determine the effect of interaction between initial abilities of PBL funds on problem solving abilities in Boolean Algebra material. The design of this study was an experiment with hypothesis testing using a two-way ANOVA test with dissimilar cells. The research subjects were students of the R3T and R3V classes in the odd semester of 2021/2022 which were obtained using the cluster random sampling technique. The results showed that there was an effect of initial ability on students' problem solving abilities, the average value of the experimental class treated with PBL was higher than the control class, and the average score of experimental class students with high initial ability was better than medium and low initial ability. . Thus, initial ability and PBL have an influence on students' problem solving abilities with the most significant difference between the categories of high initial ability and low initial ability.